PENGEMBANGAN BAHAN AJAR BERBASIS PEMBELAJARAN ABAD 21 PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA DI MTS YAYASAN MU’ALIMIN MU’ALIMAT MANYAR GRESIK - Silviatur Rahmah; Lia Nur Atiqoh Bela Dina; Moh Eko Nasrulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The development of teaching materials based on 21st century learning is based on Islamic Cultural History at MTs Mu'alimin Mu'alimat Manyar Foundation. This is due to the limitations of the teaching materials used are less clear, too long, and less interesting. Based on this background, it is necessary to develop teaching materials that can improve students' communication skills. The purpose of this study was to describe the development of teaching materials, to describe the level of effectiveness and to describe student responses to 21st century learning-based teaching materials. This study uses research and development methods with the ADDIE model. Data collection techniques used are observation, interviews, questionnaires, and tests. The subjects of this study were students of class IX. The development of teaching materials based on 21st century learning gets the percentage of validity from material experts 91%, design experts 82%, and learning experts 92%, student responses experts 92%, pre-test results were 57.8 and post-test of 78.28 which shows the post-test results have increased by 20.48. The results of the t-test analysis show that t_(count ) = 4.58 > t_table = 2.0796 so that there is a significant difference in average, then is rejected and is accepted.